TL;;DR: TEMPORALITY SHIFTS IN DIGITAL CULTURE - Koosel, Stacey May (AoIR Selected Papers of Internet Research, 2015)
Temporality is an influential aspect of digital culture, both in the design and understanding the effects of digital technologies. This essay probes ideas about temporal and spatial ordering online from the viewpoint of media ecology, digital ethnography and the philosophy of technology.